Nastawienie do imigrantów a mechanizm powstawania nowych partii politycznych – przypadek Polski - Marmola, Maciej (Political Preferences, 2016)
The attitude to immigrants and emerging of new political parties – the case of Poland The immigration is recently the most important issue influencing the fates of European Union member states. Presented article diagnoses the attitudes to immigrants arriving to EU among Polish citizens and examines how the migration crisis can affect the Polish party system according to emerging of new parties approaches. The conducted empirical research shows that majority of Polish voters are against hosting immigrants in their country. However, in contrast to the West European party systems, there is also plenty of relevant Polish parties with negative stance to immigration. Therefore, the immigration cannot be considered as a factor of party system change. Key words: new parties, political parties, party system, immigration, attitude to immigrants